THE CONCEPT OF SOCIAL NORMS IN PREVENTING GENDER-BASED VIOLENCE - Nurbayev Yodgorbek Ortiqovich; Mahmudjonov Azizxo‘ja Xurshidbek o‘g‘li; Amirullayev Alimardon Qahramon o‘g‘li (Modern American Journals, 2025)
This article examines the concept of social norms used to prevent gender-based oppression and violence in our society. In particular, the issue of preventing gender-based violence by promoting gender equality in social life, increasing education and awareness, improving legislation, helping victims, working with men, and changing social norms will be addressed. The issue of harmonizing the legal norms of this field adopted in the Republic of Uzbekistan with social norms is discussed.
Keywords: Gender, human, violence, gender equality, legislation, legal norm, social norm, human interest, civil society, right, duty, stereotype, discrimination, stigma.